Patriarki Dalihan Na Tolu dan Double Burden Perempuan Batak Toba di Desa Buhit - Krisnawati Sitanggang; Putri, Annisah; Faradilla Fadlia; Ardiansyah; Yulianda, Riki (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study examines the double burden experienced by Batak Toba women in Buhit Village, Pangururan, Samosir, as a consequence of unequal gender-based division of labor within a patriarchal cultural system. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation, involving 7 key informants (Batak Toba women), 5 male informants, as well as traditional leaders, NGO activists, and academics. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that women disproportionately assume both productive and reproductive roles, resulting in physical exhaustion and psychological stress. This condition is reinforced by the internalization of patriarchal values that legitimize women’s subordination within the customary structure of Dalihan Na Tolu. The study highlights that the persistence of the double burden is not merely an economic issue but is deeply rooted in cultural norms that normalize unequal gender relations. The implications of this research underscore the need to reinterpret Dalihan Na Tolu within a gender equality framework. Accordingly, this study recommends strengthening gender literacy, promoting a more equitable distribution of domestic labor, and implementing community-based interventions to foster more egalitarian gender relations.